Pelatihan Penerapan Inovasi Teknologi Bioflok dengan Sumber Karbon Sagu pada Kelompok Bahari Jaya Desa Soropia - Pono Suderajad; Azis, Nurdiana; Yusuf, Sarini; Purwanto, Aldi (Universitas Mataram, 2025)
Biofloc technology, with its innovative carbon source derived from sago, has significant potential for supporting the growth of microorganisms that convert pond waste into natural food. Biofloc technology in shrimp farming provides a solution for fishermen when fishing efforts are hampered by seasonal and environmental factors. This community service approach is participatory and applicable, as it is aimed at Bahari Jaya's partner community groups, who require hands-on practice. The results of the activity have shown that Bahari Jaya Group members have gained a better understanding of the basic concepts of biofloc technology and the function of carbon sources (particularly from sago) in the floc formation process by microorganisms. This has resulted in increased technical capacity and the utilization of local potential in fisheries cultivation through sago-based biofloc innovation.